2003
DOI: 10.1634/stemcells.21-4-437
|View full text |Cite
|
Sign up to set email alerts
|

Marrow Stromal Cells, Mitosis, and Neuronal Differentiation: Stem Cell and Precursor Functions

Abstract: To define relationships among marrow stromal cells (MSCs), multipotential progenitors, committed precursors, and derived neurons, we examined differentiation, mitosis, and apoptosis in vitro. Neural induction medium morphologically converted over 70% of MSCs to typical neurons, which expressed tau, neuronal nuclear antigen, neuron-specific enolase, and TUC-4 within 24 hours. A subset decreased fibronectin expression, consistent with mesenchymal to neuroectodermal conversion. More than 35% of differentiating ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(126 citation statements)
references
References 37 publications
2
119
3
2
Order By: Relevance
“…This piece of evidence, together with the fibroblastic morphology of cells, allowed us to conclude that these cells were MSCs. Neuronal differentiation of MSCs may require activation by specific exogenous factors, 19 as they were not observed expressing a neuronal phenotype after intraspinal transplantation and they probably changed to glial cells. 20 Thus, neuronal replacement in the spinal cord is feasible but requires grafting pre-differentiated stem cells or neuronal precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…This piece of evidence, together with the fibroblastic morphology of cells, allowed us to conclude that these cells were MSCs. Neuronal differentiation of MSCs may require activation by specific exogenous factors, 19 as they were not observed expressing a neuronal phenotype after intraspinal transplantation and they probably changed to glial cells. 20 Thus, neuronal replacement in the spinal cord is feasible but requires grafting pre-differentiated stem cells or neuronal precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…For neurogenesis, various inducers, alone or in combination, are involved in neurocytic differentiation in vitro of MSCs. These include retinoic acid (Cho et al, 2005), DMSO and BHA (Chu et al, 2004;Lu et al, 2004), GM1 and bFGF (Dezawa et al, 2004;Zhang et al, 2004b;Munoz-Elias et al, 2003), and 2-mercaptoethanol (2-ME) (Guo et al, 2001). It was suggested that cAMP signaling pathway should be involved in neurocytic differentiation of MSCs (Suon et al, 2004;Jori et al, 2005), but it could not rule out the synergistic effect of other signaling pathways on neurogenesis of hMSCs, in regard to neural differentiation of embryonic stem cells (Kleber et al, 2005;Bainter et al, 2001;Otero et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Accordingly, we investigated the efficiency of neural differentiation of PFs and BT-PFs in response to neuronal differentiation medium (nDM) at a morphological level monitored by timelapse video microscopy ( Figure 5a). Initially, both PFs and BT-PFs exhibited fibroblast morphologies.…”
Section: Morphological Transformation and Marker Analysis Of Pfs And mentioning
confidence: 99%